Developing prognostic models for cholesterol-related genes linked with immune infiltration in prostate cancer - Wu, Jie (Frontiers in Genetics, 2025)
BackgroundProstate cancer has a high incidence and a low 5-year survival rate. We aimed to combine cholesterol- and immune-related genes to screen prostate cancer prognosis-related genes and construct a prognostic risk model.MethodsWe obtained publicly released clinical data of prostate cancer through The Cancer Genome Atlas. Cholesterol- and immune-related genes were separately collected from the mSigDB and ImmPort databases. The prognostic model based on the immune-cholesterol-related differentially expressed mRNAs (DEmRNAs) network was constructed by univariate and multivariate Cox regression methods. Gene set enrichment analysis (GSEA), mutation landscape analysis, and immune infiltration analysis were carried out to investigate the role of immune-cholesterol-related DEmRNAs in prostate cancer.ResultsWe identified 11 immune-cholesterogenic-related DEmRNAs (C2orf88, TRPM4, SAPCD2, RHPN1, RAC3, APOF, PTGS2, TSPAN1, KLK4, ENTPD5, and C1orf64) as risk factors that were related to the occurrence and development of prostate cancer by bioinformatics analysis. Immune infiltration analysis suggested immune-cholesterol-related DEmRNAs may act in an immunomodulatory role for treatment decisions. The proportion of plasma cells, memory resting CD4 T cells, and neutrophils in the low-risk group was significantly higher than that in the high-risk group (p < 0.05). The GSEA revealed DEmRNAs were enriched in 58 Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, consisting of hematopoietic cell lineage, hypertrophic cardiomyopathy, and the JAK-STAT signaling pathway. The Gleason score of the high-risk group showed a significant difference from that of the low-risk group after clinical data analysis (P < 0.05).ConclusionThe prognostic risk model and nomogram constructed based on the immune-cholesterol-related genes had a great prognostic performance for prostate cancer.